Social-Political Co-Governance: z wprowadzeniem Boba Jessopa - Kooiman, Jan (Journal of Public Governance, 2009)
The article discusses the concept of governance based on interactions that subsist between the state and the society. The Author reviews key approaches to defining the term governance and analyses the complexity and dynamics of modern societies with special focus on the importance of social interactions to the quality of governanc. These remarks constitute the basis for the conceptualisation of three modes of socio-political governance, i.e. self-governance, cogovernance and hierarchical governance.